2023
DOI: 10.3389/fpsyg.2023.1247331
|View full text |Cite
|
Sign up to set email alerts
|

Effective altruism and the dark side of entrepreneurship

Michael Olumekor,
Muhammad Mohiuddin,
Zhan Su

Abstract: PurposeEffective Altruism (EA) has become one of the most prominent socio-philosophical movements of recent years. EA is also facing intense scrutiny due to the business practices of some of its most prominent adherents. On the other hand, the dark triad traits of Machiavellianism, narcissism and psychopathy have been getting increasing attention in entrepreneurship research. There is growing evidence that these traits can motivate entrepreneurial intention. We therefore sought to investigate if there was a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Moreover, while several studies were found using fuzzy methods to investigate the psychological traits of entrepreneurs (Brenes et al, 2021;Jiang et al, 2021;Palmer et al, 2019), no studies were found on the emerging topic of the dark triad traits of Machiavellianism, narcissism and psychopathy in entrepreneurship. A growing body of research suggests that entrepreneurs can be motivated by darker intentions (Brownell et al, 2021;McLarty et al, 2021;Olumekor et al, 2023). The additional context provided by fuzzy-set theory could further advance knowledge on these topics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while several studies were found using fuzzy methods to investigate the psychological traits of entrepreneurs (Brenes et al, 2021;Jiang et al, 2021;Palmer et al, 2019), no studies were found on the emerging topic of the dark triad traits of Machiavellianism, narcissism and psychopathy in entrepreneurship. A growing body of research suggests that entrepreneurs can be motivated by darker intentions (Brownell et al, 2021;McLarty et al, 2021;Olumekor et al, 2023). The additional context provided by fuzzy-set theory could further advance knowledge on these topics.…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurship has also been criticised for placing excessive emphasis on financial growth at the expense of sociocultural harmony and the natural ecosystem (Scheyvens et al, 2017), and for elevating people with dark character traits (Olumekor et al, 2023). Nonetheless, academic research on many areas of entrepreneurship continues to increase.…”
Section: Introductionmentioning
confidence: 99%